1999
DOI: 10.1038/sj.ijo.0801041
|View full text |Cite
|
Sign up to set email alerts
|

Fat balance and hepatic mitochondrial function in response to fat feeding in mature rats

Abstract: OBJECTIVE: To study the effects of fat feeding on fat balance and hepatic mitochondrial function in postpubertal male rats. DESIGN: Rats were fed low fat, medium fat or high fat diet for 15 days. MEASUREMENTS: Energy balance, body composition, resting metabolic rate (RMR), mitochondrial state 3 and state 4 oxygen consumption rates, succinic dehydrogenase (EC 1.3.99.1) and mitochondrial a-glycerophosphate dehydrogenase (EC 1.1.1.8) activities. RESULTS: Rats fed medium fat or high fat diet, in comparison with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
2
6
1
Order By: Relevance
“…In fact, the effect of the high‐fat lard diet to induce the increase in mitochondrial respiration capacity is evident when using nicotinamide adenine dinucleotide‐linked or lipid substrates, but not with flavin adenine dinucleotide‐linked substrate. This result is different from those previously reported in rats fed a high‐fat diet ad libitum (29), when no differences in hepatic mitochondrial oxidative capacity was found after 2 weeks of dietary treatment. This increase in hepatic mitochondrial respiratory capacity during high‐lard refeeding can be explained by the enhanced plasma FFA found in HF‐L rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, the effect of the high‐fat lard diet to induce the increase in mitochondrial respiration capacity is evident when using nicotinamide adenine dinucleotide‐linked or lipid substrates, but not with flavin adenine dinucleotide‐linked substrate. This result is different from those previously reported in rats fed a high‐fat diet ad libitum (29), when no differences in hepatic mitochondrial oxidative capacity was found after 2 weeks of dietary treatment. This increase in hepatic mitochondrial respiratory capacity during high‐lard refeeding can be explained by the enhanced plasma FFA found in HF‐L rats.…”
Section: Discussioncontrasting
confidence: 99%
“…In agreement, we have found that when a high-fat diet was given to adult rats, an increase in body lipid content was found. 37 In conclusion, our present results indicate that in rats fed a high-fat diet skeletal muscle contributes to the increased whole body lipid utilization, through an increase in lipid oxidative capacity associated with a decrease in energy coupling.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies in other animals have shown conflicting results. Studies in humans and rats have shown that REE either increases (Cooling and Blundell, 1998;Iossa et al, 1999) or remains unchanged (Corbett et al, 1986;Abbott et al, 1990) with the consumption of a HF diet compared with a LF diet. Although the reason for this discrepancy is unclear, there is evidence suggesting that stage of growth may be an important factor in determining whether REE increases in response to a HF diet.…”
Section: Discussionmentioning
confidence: 99%